Commentary: Gender differences in payments to cardiothoracic surgeons are unacceptable. (13th March 2023) - Jacobs, Jeffrey P; Nelson, Jennifer S; Fuller, Stephanie M; Antonoff, Mara B; Karamlou, Tara; Molena, Daniela; Preventza, Ourania; Blackmon, Shanda; Romano, Jennifer
: Every effort must be made by the leaders in our field, as well as by every individual cardiothoracic surgeon, to assure equal opportunity for all cardiothoracic surgeons, regardless of race, gender or any other sociodemographic source of bias. Every effort must be made by every surgeon, not just those in particular leadership roles. Opportunities for advancement must be equal in multiple domains, including clinical practice, patient referral, clinical leadership, academic leadership, institutional leadership and leadership in professional medical and surgical societies. Such actions to minimize bias and promote inclusivity will also ensure that cardiothoracic surgical care is provided by a workforce that represents the diversity of patients whom we serve. In the final analysis, it is an absolute fact that gender differences in payments to cardiothoracic surgeons are absolutely unacceptable and cannot be tolerated. Abstract : Dr.